2019
DOI: 10.4081/hr.2019.7912
|View full text |Cite
|
Sign up to set email alerts
|

Use of Catridecacog in a Patient with Severe Factor XIII Deficiency Undergoing Surgery

Abstract: Despite many articles regarding the antihemorrhagic treatment and prophylaxis, there is a lack of experience about how to best conduct major surgical procedures in patients with congenital factor XIII (FXIII) deficiency. Here we report a case of surgery (right inguinal hernia, complicated by heaviness and pain) performed in a patient with FXIII deficiency, receiving recombinant FXIII prophylaxis (Catridecacog 35 UI/kg every 28±2 days). Our experience shows that Catridecacog can be used safely and effectively n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This is available in the form of plasma-derived FXIII, that is, cryoprecipitates and fresh frozen plasma 5. However, recently various reports of using recombinant FXIII has been published achieving successful haemostasis 6 7. To our knowledge, only a single case of bilateral intraorbital haemorrhage after strabismus surgery in FXIII deficiency has been reported in the literature, which is currently unavailable in India 8.…”
Section: Discussionmentioning
confidence: 99%
“…This is available in the form of plasma-derived FXIII, that is, cryoprecipitates and fresh frozen plasma 5. However, recently various reports of using recombinant FXIII has been published achieving successful haemostasis 6 7. To our knowledge, only a single case of bilateral intraorbital haemorrhage after strabismus surgery in FXIII deficiency has been reported in the literature, which is currently unavailable in India 8.…”
Section: Discussionmentioning
confidence: 99%
“…However, the factor XIII content of 1 mL cryoprecipitate is too low to prevent bleeding 9) . A study reported the presence of α-subunit mutation and congenital factor XIII activity level under 5%, in which a dose of 35 units/ kg recombinant factor XIII (NovoThirteen ® , 2500 units/vial; Novo Nordisk, Bagsvaerd, Denmark) was considered suitable and safe 10) .…”
Section: Diagnosis and Treatmentmentioning
confidence: 99%